Changing church and state relations in Hong Kong, 1950-2000 - Leung, Beatrice (Hong Kong culture and society., 2003)
The book gave detailed account of Hong Kong's church-state relationship in metamorphosis. It should be an important text for students in both political science and China studies, and especially in the history of Hong Kong.